Estudos polifásicos de populações de Phormidioideae (Oscillatoriales, Cyanobacteria) - Martins, Mariéllen Dornelles [UNESP] (2014)
The Phormidioideae members are found in terrestrial and aquatic environments, growing on a wide variety of substracts (soil, rocks, barks of trees and artificial objects). According to the usual classification, the subfamily comprises ten genera, of which Phormidium, Trichodesmium, Arthrospira, Porphyrosiphon e Planktothrix are the most abundant in number of species. Due to its relatively simple morphology, the members of Phormidioideae form a taxonomically complex group and its morphological plasticity is related to environmental factors, making confusing the distinction of genera and species. This study aimed to contribute to the taxonomic knowledge of the group through floristic survey in different regions of Brazil. The collected material was used for detailed taxonomic group, using molecular tools (16S rRNA gene and the 16S-23S ITS), besides the classic morphological tools. The identification studies revealed 27 species, 22 belong to Phormidium, three to Porphyrosiphon, one to Planktothrix and one to Planktothricoides. Among them, Phormidium animale is the first occurrence in Brazil and 11 are new species to science. Morphological and molecular studies reinforce that the division of genera and species of Phormidioideae is still quite confusing. While the morphological markers used did not reflect the evolutionary history of the group, the molecular proved taxonomically valid and should be considered the basis for the construction of classification of Phormidioideae. Analyses revealed that the subfamily is polyphyletic. Porphyrosiphon is genetically supported genus, but P. notarisii is a collective species. The flora proved to be diverse, with seven new genera morphologically and genetically defined